(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2022)
Annotation. Introduction. The article investigates the main problems in the field of social protection of the population in Ukraine that require an immediate solution. The theoretical approach to the financial support of the social sphere is considered. The reasons for the negative impact on the implementation of budget policy in the social protection system are investigated. The financing of social protection and social security, health and education from state and local budgets of Ukraine is analyzed. Changes in the system of social protection through the transformation of financing of the social protection system are determined. The purpose of the article. It is worth exploring the financial support of social services in Ukraine in recent years. It is also worth offering possible ways to counteract the underfunding of the social sphere from the budgets of different levels. Results. Formation of national social security in the system of public finance management should be carried out on the basis of the system of fiscal norms and to be focused; to ensure effective forms of supporting various social groups that require social protection; transition to cash provision of welfare; Personal assistance to the state is included in income of individuals and families. Taking into account that wages are still the main source of income in Ukraine, it is necessary to increase its share in income, paying special attention to minimal hourly remuneration. Conclusions. The main reason for the negative impact on the implementation of fiscal policy in the social security system is mainly reflected in the implementation of the budget expenditures approved by the state. In addition, during the research process, we have found that in the state budget of Ukraine, social security expenditures and social insurance funds have increased more than doubled over the past five years, indicating the lack of funds in this area.